2009
DOI: 10.1007/s00234-009-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

Wilson’s disease: two treatment modalities. Correlations to pretreatment and posttreatment brain MRI

Abstract: From the neurological point of view, there was no difference on the evolution between the group treated exclusively with D-P and the one treated with Zn. Analysis of MRI scans with longer intervals after the beginning of treatment depicted a trend for neuroimaging worsening, without neurological correspondence, among patients treated with Zn. Neuroimaging pattern of evolution was more favorable for the group that received exclusively D-P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…In general, we found less frequent brain MRI abnormalities compared with previous reports (King et al 1996; Da Costa et al 2009; Prashanth et al 2005; Magalhaes et al 1994; Saatci et al 1997; Prayer et al 1990; Kozic et al 2003), which may be due to differences in the methods of patient selection, the examination performed at diagnosis, patients with all of the clinical manifestations (hepatic neuropsychiatric and presymptomatic), and the large number of cases. Until now, most studies have presented data obtained mainly from neurological patients (Machado et al 2006; King et al 1996; Da Costa et al 2009; Prashanth et al 2005; Magalhaes et al 1994; Saatci et al 1997), with very few patients exhibiting the hepatic form of the disease (Kozic et al 2003).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…In general, we found less frequent brain MRI abnormalities compared with previous reports (King et al 1996; Da Costa et al 2009; Prashanth et al 2005; Magalhaes et al 1994; Saatci et al 1997; Prayer et al 1990; Kozic et al 2003), which may be due to differences in the methods of patient selection, the examination performed at diagnosis, patients with all of the clinical manifestations (hepatic neuropsychiatric and presymptomatic), and the large number of cases. Until now, most studies have presented data obtained mainly from neurological patients (Machado et al 2006; King et al 1996; Da Costa et al 2009; Prashanth et al 2005; Magalhaes et al 1994; Saatci et al 1997), with very few patients exhibiting the hepatic form of the disease (Kozic et al 2003).…”
Section: Discussioncontrasting
confidence: 54%
“…Until now, most studies have presented data obtained mainly from neurological patients (Machado et al 2006; King et al 1996; Da Costa et al 2009; Prashanth et al 2005; Magalhaes et al 1994; Saatci et al 1997), with very few patients exhibiting the hepatic form of the disease (Kozic et al 2003). We believe that our data are not deeply biased by our hospital speciality because we had approximately 30 % of patients with hepatic manifestation at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Copper accumulation in the brain can induce changes such as myelin degeneration, gliosis, and profound neuronal loss. 10,11 Among all brain structures (including the cerebellum), the gray matter in the basal ganglia [11][12][13][14][15] is affected the most, followed by the brainstem (red nucleus and substantia nigra [SN]) 16,17 and the cortex (especially the frontal lobes and the parietooccipital zones). 14,18 Additionally, emotion research has revealed that the psychiatric impairments of WD, including emotional lability, personality disorders, and mania, are caused by abnormalities in the limbic system 19 and basal ganglia.…”
mentioning
confidence: 99%